SPECIFIC FEATURES OF EFFECTIVE PERFORMANCE OF FUNCTIONS IN A PROJECT TEAM - Khalilov Samandar Abdurashidovich (Scholars Digest Publishing, 2024)
The article covers the definitions of a project and the importance of a project team. The key factors of a project team's success are discussed. These include clarity of goals and strategy, effective communication, clarity of roles and responsibilities, education and training, external cooperation, adaptability to changes, as well as development and analysis. The article substantiates the necessity of properly organizing these factors for effective work in a project team. It is emphasized that setting project goals, communication systems, team members' responsibilities, training programs, external partnerships, the team's adaptability to changes, as well as properly organizing development and analysis activities are crucial. Thus, the article reveals these key factors that ensure effective work in a project team and suggests ways to successfully implement projects by adhering to these factors.
Keywords: Project team, Effective performance of functions, Agile methodology, Cross-functional teams, Online platforms, Data analytics, Feedback, Creative approaches, Virtual teams, Public-private partnership, Investment projects, Artificial intelligence, Automation of management processes.